Human DP and EP2 prostanoid receptors take on distinct forms depending on the diverse binding of different ligands. (29th September 2016) - Suganami, Akiko; Fujino, Hiromichi; Okura, Iori; Yanagisawa, Naoki; Sugiyama, Hajime; Regan, John W.; Tamura, Yutaka; Murayama, Toshihiko
Abstract : Human D‐type prostanoid (DP) and E‐type prostanoid 2 (EP2) receptors are G protein‐coupled receptors and are regarded as the most closely related receptors among prostanoid receptors because they are generated by tandem duplication. The DP receptor‐cognate ligand, prostaglandin D2 (PGD2 ) has the ability to activate not only DP receptors but also EP2 receptors. Likewise, the EP2 receptor‐cognate ligand, prostaglandin E2 (PGE2 ) has the ability to activate DP receptors in addition to EP receptors in order to stimulate cAMP formation. However, since PGD2 and/or PGE2 activate DP and EP2 receptors to similar maximal levels, that is, their similar efficacies, differences between the ligands in each receptor have not yet been determined in detail except for their different affinities. Herein we demonstrated, using an in silico simulation to predict binding patterns among DP or EP2 receptors and PGD2, PGE2, or prostaglandin F2α as the reference prostanoid, that DP and EP2 receptors plausibly take on distinct forms depending on the diverse binding of different ligands. Since these ligands have the potential to make these receptors form distinct conformations with discrete signaling pathways, they are consequently regarded as endogenous biased ligands. Moreover, by using functional assays, the susceptibilities of the DP receptors to the noncognate ligands were approximately 10 times lower than those of EP2 receptors. Thus, EP2 receptors seem to be able to distinguish endogenous ligands better than DP receptors, thereby both receptors are plausibly gaining role‐sharing functions with respect to one another as the copies of duplicated gene. Abstract : Predicted 3D structures of DP and EP2 receptors. Y199 on transmembrane (TM) 5 and R284 on TM6 in DP receptors, as well as Y196 on TM5 and E288 on TM6 in EP2 receptors, are key amino acids to form hydrogen bonding interactions. These interactions make these receptors form distinct conformations by endogenous biased ligands such as PGD2, PGE2, and PGF2α .